2018
DOI: 10.1007/s12529-018-9736-x
|View full text |Cite
|
Sign up to set email alerts
|

Testing an Online, Theory-Based Intervention to Reduce Pre-drinking Alcohol Consumption and Alcohol-Related Harm in Undergraduates: a Randomized Controlled Trial

Abstract: Reductions in outcome measures were likely related to elements common to each condition (i.e., provision of national guidelines, assessment of outcome measures, e-mail summary, and SMS messages), rather than motivational and volitional components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 85 publications
0
10
0
2
Order By: Relevance
“…El estudio de Caudwell et al, (25) no pudo probar la ecacia de una intervención en línea basada en la teoría que comprende componentes motivacionales (apoyo a la autonomía) y volitivos (intención de implementación). De la misma manera, Bedendo et al, (26) evaluaron los efectos de los dos componentes principales de una retroalimentación normativa personalizada, sin embargo, sus resultados no fueron concluyentes.…”
Section: Intervenciones No Efectivasunclassified
“…El estudio de Caudwell et al, (25) no pudo probar la ecacia de una intervención en línea basada en la teoría que comprende componentes motivacionales (apoyo a la autonomía) y volitivos (intención de implementación). De la misma manera, Bedendo et al, (26) evaluaron los efectos de los dos componentes principales de una retroalimentación normativa personalizada, sin embargo, sus resultados no fueron concluyentes.…”
Section: Intervenciones No Efectivasunclassified
“…Asimismo, los resultados indican un mayor riesgo de incursionar en la previa, o de consumir en mayor cantidad, en los adolescentes que perciben un mayor involucramiento en esta práctica por parte de sus amigos cercanos. Al respecto, intervenciones basadas en el enfoque de normas sociales (Borsari et al, 2016;Caudwell et al, 2018), incluso a nivel local (Pautassi y Bonino, 2020), sugieren que esta podría ser una prometedora alternativa de intervención para reducir la conducta de previa.…”
Section: Conclusionesunclassified
“…Implementation intentions interventions can assume a variety of different formats. Type of implementation intentions can be oral or in writing, on paper or on screen (sometimes online), self-generated by people completing the intervention or prespecified by the researchers or clinicians, or pre-specified situation and self-generated solutions (Armitage 2009;Armitage 2015;Caudwell et al 2018;Hagger et al 2012a).…”
Section: Implementation Intentions To Promote Health Behaviourmentioning
confidence: 99%
“…Firstly, data was pooled from 16 studies that reported unadjusted data (Arden and Armitage, 2012;Armitage, 2009;Armitage, 2015;Armitage and Arden, 2012;Armitage and Arden, 2016a;Armitage and Arden, 2016b;Armitage et al, 2011;Armitage et al, 2014;Caudwell et al, 2018;Ehret and Sherman, 2018;Hagger et al, 2012a;Hagger et al, 2012b (3 samples); Murgraff et al, 2007;Rivis et al, 2013) and included 2055 individuals (students and general population). The effect size for alcohol use was g=0.31 (95% CI: 0.21, 0.42), p< .001, indicating that implementation intentions had a small but significant effect in reducing alcohol consumption (Figure 2).…”
Section: Alcohol Consumptionmentioning
confidence: 99%